Continuity and change in the Community Development Employment Projects Scheme (CDEP). Issue 1 (March 2013) - Hunter, Boyd; Gray, Matthew
Abstract : The Community Development Employment Projects (CDEP) scheme is an example of an Indigenous‐specific program that combines community development and labour market program elements. This paper describes the nature of CDEP employment in 2008 and the extent to which it changed between 1994 and 2008. The paper also compares a selection of economic and social outcomes of CDEP participants with those of persons who were employed outside of CDEP, unemployed and not‐in‐the‐labour‐force (NILF) in 2008 and the extent to which these associations changed between 1994 and 2008. This paper also aims to assess the extent to which CDEP participation is consistent with the community development objectives of the scheme. The analysis shows that the nature of the jobs in which CDEP participants work and the experiences it provides to workers have changed little despite substantial changes in underlying policy settings. CDEP participation is associated with the maintenance of language and culture as well as facilitating an ongoing connection to traditional lands. Participation in the scheme is associated with better social and economic outcomes compared to those of the unemployed or those NILF, but much worse outcomes than those for people working in non‐CDEP employment.